2013
DOI: 10.1037/a0032562
|View full text |Cite
|
Sign up to set email alerts
|

Build-up of auditory stream segregation induced by tone sequences of constant or alternating frequency and the resetting effects of single deviants.

Abstract: A sequence of constant-frequency tones can promote streaming in a subsequent sequence of alternating-frequency tones, but why this effect occurs is not fully understood and its time course has not been investigated. Experiment 1 used a 2.0-s-long constant-frequency inducer (10 repetitions of a low-frequency pure tone) to promote segregation in a subsequent, 1.2-s test sequence of alternating low- and high-frequency tones. Replacing the final inducer tone with silence substantially reduced reported test-sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 57 publications
1
31
0
Order By: Relevance
“…In our earlier behavioral study (which used the same animals and same experimental stimuli as in the current study) (Christison-Lagay and Cohen, 2014), we included three control conditions that support that monkeys stream the stimuli used in the current paradigm. First, the monkeys were more likely to report “large” frequency differences with longer listening times (Christison-Lagay and Cohen, 2014), similar to human listeners who are also more likely to report two streams with longer listening times (Micheyl et al, 2005) and consistent with the idea that one’s perception of two streams “builds up” over time (Micheyl et al, 2005; Haywood and Roberts, 2013). Second, similar to human listeners (Elhilali et al, 2009; Micheyl et al, 2013), when the tone bursts were presented simultaneously (vs. asynchronously as shown in Figure 1A ) and the frequency difference was large (which normally elicits reports of “two auditory streams”), the monkeys’ reports were biased toward those of when they had heard a “small” frequency difference (Christison-Lagay and Cohen, 2014).…”
Section: Discussionmentioning
confidence: 57%
“…In our earlier behavioral study (which used the same animals and same experimental stimuli as in the current study) (Christison-Lagay and Cohen, 2014), we included three control conditions that support that monkeys stream the stimuli used in the current paradigm. First, the monkeys were more likely to report “large” frequency differences with longer listening times (Christison-Lagay and Cohen, 2014), similar to human listeners who are also more likely to report two streams with longer listening times (Micheyl et al, 2005) and consistent with the idea that one’s perception of two streams “builds up” over time (Micheyl et al, 2005; Haywood and Roberts, 2013). Second, similar to human listeners (Elhilali et al, 2009; Micheyl et al, 2013), when the tone bursts were presented simultaneously (vs. asynchronously as shown in Figure 1A ) and the frequency difference was large (which normally elicits reports of “two auditory streams”), the monkeys’ reports were biased toward those of when they had heard a “small” frequency difference (Christison-Lagay and Cohen, 2014).…”
Section: Discussionmentioning
confidence: 57%
“…However, Beauvois and Meddis (1997) used a constant frequency induction sequence with no silence between the induction and test sequence. Haywood and Roberts (2013), in contrast, showed that an alternating frequency induction sequence had less of an effect on the perception of streaming. Even if the effect was smaller, our neurophysiologic results may be partially explained by their results.…”
Section: Discussionmentioning
confidence: 99%
“…Even for a context of a single stream of tones, say A_A_A_A_, that would alone promote segregation for subsequent test triplets ABA_ ABA_…, similar disruptions as above at the end of the context sequence lead to integration, as if the effect of the context was undone (Rogers and Bregman, 1993, 1998; Beauvois and Meddis, 1997). Also, a single deviant A' at the end of an A_A_A_…context can reduce or eliminate the expected bias toward segregation (Roberts et al, 2008; Haywood and Roberts, 2010, 2013). So while these various disruptions favor integration and may a priori lead one to a generalized expectation that a single transient distractor tone (between triplets) or a single deviant tone (within a triplet) should also promote integration, we found the opposite — promotion of segregation in the subsequent triplets.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless our results do not contradict these previous studies. Studies looking at the effects of deviant tones did so by placing these at the end of a single stream context (Roberts et al, 2008; Haywood and Roberts, 2010, 2013); in our study we placed the deviant or distractor at the end of context triplets. Thompson et al (2011) included an experiment with a single delayed-onset deviant B tone, but did not report promotion of segregation or resetting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation